Case Report: Infantile Bullous Pemphigoid: Triggering by COVID-19 Is Speculative - Rosińska-Więckowicz, Anna; Jałowska, Magdalena; Bowszyc-Dmochowska, Monika; Dmochowski, Marian (Frontiers in Medicine, 2021)
Bullous pemphigoid (BP) is a cutaneous disease triggered by numerous stimuli, where genetic milieu-influenced autoimmunity to hemidesmosomal proteins, namely, BP180 and/or BP230 initiate an inflammation leading to dermal-epidermal junction (DEJ) enzymatic pathological remodelling. Here, to the best of our knowledge, we present the first case of an infantile BP apparently triggered by COVID-19. BP should be included in differential diagnosis of infantile rashes showing blisters or vesicles or both as well as their prodromal and evolutionary lesions. Possible triggers, such as coronavirus disease 2019 (COVID-19), of BP in infancy should be identified and properly dealt with.